Use and Perceptions of the Internet for Sexual Information and Partners: A Study of Young Men who Have Sex with Men - Kubicek, Katrina (2010)
The Internet has opened many doors with its accessibility to information, entertainment and web-based communities. For young men who have sex with men (YMSM), the Internet can provide access to information on relevant sexual behavior and health information, stories from other men about relationship issues, and a venue for locating potential sexual and dating partners. Understanding YMSM’s motivations for going online for information, advice or sexual relationships, is important as the Internet becomes increasingly used not only as a space to find sexual partners, but also as a venue for HIV and STI interventions. Having an understanding of the risks associated with searching for partners online, and how and why YMSM use the Internet for a variety of purposes, can inform the development of more effective Internet-based risk reduction programs. This manuscript presents qualitative and quantitative data from the Healthy Young Men’s Study, a longitudinal study of an ethnically diverse cohort of 526 YMSM. Qualitative interviews (N=24) described not only the prevalence of using the Internet for finding sexual partners and the possible benefits and risks associated with that practice, but also the processes and perceptions of using this mechanism. Our data indicate that YMSM use the Internet to find information related to sex and sexuality, seek friendships, sexual partners as well as “hook-ups” or casual sex. Findings are presented in relation to how YMSM researchers and interventionists can identify how to most effectively reach YMSM through online methods.